Well-Being Literacy in the Academic Landscape: Trioethnographic Inquiry Into Scholarly Writing - Narelle Lemon; Jacqui Francis; Lisa M. Baker (Brock University, 2024)
Writing well and being well as academic writers is rarely spoken about, often hidden, and at times evaded. We believe that developing, maintaining, and growing well-being literacy not only engages the act but also allows awareness, reflection, and metacognitive thinking that enable mindful writing for well-being. Well-being literacy, the capacity to understand and employ well-being language for personal, collective, and global well-being, intrigues us. It encompasses nurturing, sustaining, and safeguarding well-being for individuals, groups, and systems to thrive. As scholars delving into well-being literacy, we, a diverse collective from across higher education career trajectories, investigate its role in scholarly writing and our academic realities. Our focus lies in unraveling the paradoxes inherent in higher education, particularly as researchers and writers. In this paper, we examine our own stories as a trioethnography and the impact of our writing practices on our own professional and personal lives. By doing so, we reveal the place of vulnerability, relationships, and meaning in who we are and are becoming as academic scholars. Guiding principles are shared with peers and colleagues in how they might cultivate writing practices while valuing and embodying well-being in the higher education space.